2010
DOI: 10.1242/jcs.053694
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the transcription site to the nuclear pore: a multi-tether process that regulates gene expression

Abstract: SummaryIt is now well established that the position of a gene within the nucleus can influence the level of its activity. So far, special emphasis has been placed on the nuclear envelope (NE) as a transcriptionally silent nuclear sub-domain. Recent work, however, indicates that peripheral localization is not always associated with repression, but rather fulfills a dual function in gene expression. In particular, in the yeast Saccharomyces cerevisiae, a large number of highly expressed genes and activated induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 109 publications
2
59
0
2
Order By: Relevance
“…However, pore clustering was not sufficient for RNA retention, as an N-terminal truncation of NUP133, which retained the pore clustering phenotype, did not retain the poly(A) + mRNA. This was reflected in our results as the nuclear poly(A) + levels were wild type (7.5% 6 1.9%) in the NUP133DN strain (Fischer et al 2002;Libri et al 2002;Dieppois and Stutz 2010). While many of the retention defects were quantitatively similar, we observed variation within single mutant populations.…”
Section: Differential Poly(a)supporting
confidence: 60%
See 1 more Smart Citation
“…However, pore clustering was not sufficient for RNA retention, as an N-terminal truncation of NUP133, which retained the pore clustering phenotype, did not retain the poly(A) + mRNA. This was reflected in our results as the nuclear poly(A) + levels were wild type (7.5% 6 1.9%) in the NUP133DN strain (Fischer et al 2002;Libri et al 2002;Dieppois and Stutz 2010). While many of the retention defects were quantitatively similar, we observed variation within single mutant populations.…”
Section: Differential Poly(a)supporting
confidence: 60%
“…As described previously, the nuclear poly(A) + signal in many strains affecting mRNA export was not uniformly distributed in the nucleus, but showed a granular staining. This granular poly(A) + staining, commonly seen in the mex67-5, Dmlp1, Dmlp2, Dnup60, and Dnup2 strains, might likely be the result of mRNAs retained at the site of transcription, a phenotype that has been described for a subset of mRNA export and processing mutants (Fischer et al 2002;Libri et al 2002;Dieppois and Stutz 2010). The Dnup133 strain showed accumulation of poly(A) + RNA at one or two foci within the nucleus.…”
Section: Differential Poly(a)mentioning
confidence: 75%
“…Subsequently, a series of genomewide studies suggested that nuclear pore components bind highly active genes (Casolari et al 2004(Casolari et al , 2005Schmid et al 2006). While some promoter-bound pore components are not stably bound to NPCs (Dilworth et al 2005;Therizols et al 2006;Ruben et al 2011), the tagging and localization of specific inducible genes confirmed that some genes indeed shift to NPCs upon activation (for reviews, see Akhtar and Gasser 2007;Taddei 2007;Dieppois and Stutz 2010;Egecioglu and Brickner 2011) (Figure 6).…”
Section: Gene Activationmentioning
confidence: 98%
“…Embedded in the inner membrane of this nuclear envelope one finds different structures and proteins that anchor chromosomes, including the SPB and nuclear pores (reviewed in Dieppois and Stutz 2010). Trafficking between the nucleoplasm and the cytoplasm occurs through 200 NPCs, which enable the free diffusion of small molecules as well as the regulated transport of macromolecules by the importin machinery (Alber et al 2007;D'Angelo and Hetzer 2008;Aitchison and Rout 2012).…”
Section: Unique and Conserved Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation